A new wrasse, Novaculops compressus n. sp. (Perciformes: Labridae), from the western Pacific Ocean - Fukui, Yoshino (Zootaxa, 2020)
A new sandy, Novaculops compressus n. sp. is described on the basis of two specimens collected from Yoron Island, Japan and Panay Island, the Philippines. The new species is characterized by IX, 12 dorsal-fin rays, III, 12 anal-fin rays, 12 or 13 pectoral-fin rays, interrupted lateral line, 12 + 5 pored lateral-line scales, 4 scale rows above lateral line, 9 scale rows below lateral line, 16 total gill rakers, snout length 11.1% of standard length (SL), orbit diameter 10.0–10.1% SL, body depth 30.9% SL, anal-fin base length 36.2–37.6% SL, first dorsal-fin spine length 6.4–7.0% SL, pectoral-fin axil black, and first two dorsal-fin membranes black. This species is sympatric with N. sciistius in Kagoshima, Japan.